Moringa oleifera Leaf Powder Dietary Inclusion Differentially Modulates the Antioxidant, Inflammatory, and Histopathological Responses of Normal and Aeromonas hydrophila-Infected Mono-Sex Nile Tilapia (Oreochromis niloticus) - El-Kassas, Seham; Aljahdali, Nesreen; Abdo, Safaa E.; Alaryani, Fatima S.; Moustafa, Eman M.; Mohamed, Radi; Abosheashaa, Wesam; Abdulraouf, Esraa; Helal, Mohamed Atef; Shafi, Manal E.; El-Saadony, Mohamed T.; El-Naggar, Karima; et al. (Frontiers in Veterinary Science, 2022)
This study aimed to detect the impact Moringa oleifera leaves dietary inclusion on the antioxidant and innate immune responses of mono sex Nile tilapia fingerlings. A total of 180 fingerlings were allocated in random method into three groups with triplicate each. The1st group fed basal diet (BD) free of moringa while the 2nd and 3rd fed BD containing M. oleifera leaves at 5 and 10% of the diet, respectively. After 6 weeks of feeding, fish were randomly redistributed into 4 replicates and rested for 24h. Then, 2 replicates were infected with 0.2 mL of A. hydrophila suspension (1.8 × 106 CFU/mL) while the others were injected with PBS. Healthy fish fed moringa showed enhanced immune response manifested by significant increases of phagocytic and lysozyme activities with a marked lowering of H/L ratio (P < 0.05). Additionally, significant alterations of the lymphocytic and heterophilic population in circulation and increased infiltration in tissue such as spleen were noticed. Also, M. oleifera significantly upregulated the antioxidants; CAT and GPx, proinflammatory cytokines; IL1-β, IL-8 and IFN-γ relative mRNA levels. Conversely, following A. hydrophila, moringa caused downregulations of IL1-β, IL-8 and IFN-γ expression levels besides lowered the CAT and GPx mRNA levels. Additionally, a marked reduction of leukocytic infiltration plus a significant improvement of the degenerative changes in intestinal architecture have occurred. So, M. oleifera leaves can be utilized safely in fish diet to enhance immune response under normal health conditions and lower infection-associated inflammatory response.